Operasi Sedot Lemak Pipi (Facial Liposuction) Perspektif Maqāṣid al-Syarī’ah: Cheek Liposuction Surgery (Facial Liposuction) Maqāsid al-Syarī'ah Perspective - Ulfa Qorina; Nuraeni Novira; Jujuri Perdamaian Dunia (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2022)
This study aims to determine and understand the legal concept of cheek liposuction surgery from the perspective of Maqāṣid al-Syarī'ah. This research uses descriptive qualitative research which focuses on library research using normative juridical and phenomenology approaches. The results of this study are: first: Maqāṣid al-Syarī'ah in determining the law is very important because when determining the law on a problem it must consider the benefits and harms. The general purpose of Islamic law is to realize and realize benefits both in this world and in the hereafter, namely by taking benefits and rejecting harm; second, the law of cheek liposuction surgery is forbidden if it is aimed at beauty and beauty and is changing Allah's creation. As for the permissibility of doing liposuction of the cheek in an emergency.